METHODOLOGICAL APPROACHES FOR EVALUATING THE DAYLIGHT PERFORMANCE OF COMPLEX FACADE FORMED AND OBSTRUCTED ROOMS ACCORDING TO EN 17037 STANDARD - Konuk Tastan, Gulcin Gulsum; Iplik, Isil; Uyduran, Hizir Gokhan; Yagmur, Sensin (MIDDLE EAST TECHNICAL UNIV, 2024)
Effective use of daylight is essential for human health and energy efficiency. Although, that daylight performance is evaluated under four main categories in the EN 17037:2022 Daylight in Buildings Standard, frequently cited in many daylighting studies, have not considered all the criteria. In the literature, it is observed that simple volumes with single openings or unobstructed box-shaped forms are generally preferred, and the detailed guidelines proposed in the EN 17037:2022 Standard are not utilized in these studies. Furthermore, the standard recommends that the daylight provision performance is calculated at one-hour intervals throughout the year and that the evaluations are made based on the achievement of target illuminance levels. Researchers utilize solstice dates because completing these calculations with non-parametric tools is timeconsuming. The modules of parametric calculation tools include sDA/ UDI criteria which are used in LEED/BREEAM certification systems, and which enable rational analyses instead of illuminance levels. Therefore, there is a need to develop methods for parametric workflows that can evaluate illuminance data at one-hour intervals throughout the year, as well as for comprehensive analyses of the daylight performance of complex-shaped buildings in accordance with the recommendations provided in the standard. In this study, the daylight performance of a theoretical living room with a complex shape and multiple openings, a segmented facade, varying wall thickness, and surrounding obstructions, is examined in terms of the four criteria specified in the standard. Thus, it is aimed to develop methodological approaches that fulfil the detailed guidelines outlined in the standard. For the daylight provision criteria, both methods recommended in the standard are considered, and a parametric workflow is implemented in the Rhinoceros/Grasshopper program. The view out criteria are considered to encompass three subcategories and a fisheye camera is used via software to determine the visible layers. For the exposure to sunlight criteria, the total duration of three openings with different obstruction conditions is calculated, and the required glare protection class of the equipment for the glare protection criteria is determined. This study would contribute to the evaluation of the daylight performance of complex forms with varied obstruction conditions, considering all the criteria specified in the standard, as well as reducing time losses in daylight studies through the developed methods.
Keywords: DESIGN; BUILDINGS; MELATONIN; Architecture